The Concept of the Family and its Composition in the Iraqi Personal Status Law, a Comparative Study with International Conventions Related to Human Rights - Saleh, Khaled Muhammad; Karim, Bokan Abu Bakr (Journal of Legal and Political Studies, 2018)
This study deals with the concept of the family and the impact of international conventions on this concept and its work on changing the concept of the family as it departs from the stereotypical interpretation that has been established for it and the call for absolute equality between men and women in the composition of the family. Since the inception of the United Nations, its vision of the meaning of the family and its forms has gone through many stages. It has begun to recognize that it is the natural and fundamental group unit of society and that women and men have the right to conclude a marriage contract when they reach the age specified in accordance with their national law. For the composition of the family, and this is consistent with the concept of family in the Iraqi Personal Status Law No. 188 of 1959. In recent years, many international documents adopted by the United Nations have dealt with this concept from a different perspective and by recognizing the existence of other types of family that are made up of men and women outside marriage and the equal rights of children born as a result of this relationship. Marriage was one of the human rights not exclusively as a contract between a man and a woman. In this context, the international conventions and conferences related to the family and the state parties to enact legislation that recognizes the modern concept of the family and abolishes the existing ones.
Keywords: International Conventions; interpretation; marriage contract; United Nations